Patterns of Religious Magic Customary Law in Traditional Sundanese Wiwitan Marriage in West Java - Kusmayanti, Hazar; Kania, Dede; Sulastri, Dewi; Suhartini, Endeh; Rajamanickam, Ramalinggam (Faculty of Law, Universitas Pattimura, 2023)
Introduction: The marriage law was carried out through a long process, due to, religions, or national interests. Marriages in Indonesia are not only based on the beliefs of official religions in Indonesia, but there are also marriages carried out by the Faith in God Almighty. One of the faith streams in Indonesia is the Sunda Wiwitan school. Purposes of the Research: In this study, researchers were interested in examining magical religious practices in the marriages of the Sunda Wiwitan indigenous people of West Java.Methods of the Research: The approach method used in this study is normative juridical research through legal principles, legal systematics, legal synchronization, and legal comparison. Results of the Research: The results showed that the marriage practice of indigenous peoples who live the Sunda Wiwitan faith is still thick with its customary rituals, this is done as a process in fulfilling the practice of marriage as one of the important life phases for the Sunda Wiwitan community. The characteristics of marriage of indigenous peoples who live in Sunda Wiwitan in West Java, having the concept of marriage containing the meaning of the beginning of the single end so sawaji (initially one, finally so unified), Marriage must be monogamous which is approved by the parents of both parties and the prohibition of marriage for Sunda Wiwitan believers is to marry between nations (marrying people outside Indonesia).